Using future music teachers’ art-pedagogy in art lessons in primary school - Panasenko, Yuliia; Holota, Marharyta (Professional Art Education, 2026)
Due to the radical changes in education affecting all levels of the educational system, the issue of training future specialists, particularly those who will educate the future generation of the country, has become increasingly important. Special attention is paid to primary school, as younger pupils represent the first stage of secondary education. Therefore, there is a growing need to support the development of children’s potential through the use of art-pedagogical methods in art lessons at primary school. The purpose of the study is to substantiate the significance of using art-pedagogical methods in art lessons in primary school and to determine their role in the development of younger pupils’ creative potential. Methods & methodology. Analysis of scientific and pedagogical literature, generalization of theoretical principles of art pedagogy, characterization and analysis of art-pedagogical methods, and comparison of their practical application in art lessons at primary school. Scientific significance. The essence of the concepts “art pedagogy” and “art-pedagogical methods” has been revealed; the main aspects of art pedagogy have been identified, and the problems of using art-pedagogical methods in primary school have been characterized. Particular attention has been paid to the relevance of developing children’s creative potential through the means of art. Results. Art-pedagogical methods used in art lessons at primary school have been analyzed, and examples of their application have been provided. It has been established that the use of art-pedagogical methods contributes to pupils’ creative development, helps reveal their potential, and increases the effectiveness of the educational process. Conclusions. The use of art-pedagogical methods in art lessons at primary school is relevant and pedagogically appropriate. They contribute to the development of younger pupils’ creative abilities, the formation of their emotional sphere, and create conditions for the harmonious development of personality. The application of artistic methods increases pupils’ interest in learning and activates their cognitive activity. Art-pedagogical approaches help create a positive classroom atmosphere and promote children’s self-expression. Further implementation and improvement of art-pedagogical methods in the modern educational process of primary school are considered promising.